Role of C-Reactive Protein in Peripheral Arterial Disease - Ibaram, Dr. Robert Skopec (International Journal of Innovative Research in Medical Science, 2018)
Objective: To review the role of elevated C - reactive protein (CRP) as a marker for predicting the development of Peripheral Arterial Disease (PAD). Methods: An online search was conducted using the most trusted medical data base PubMed and the articles published in peer-reviewed journals within the last 5 years (from the year 2005 to date) to collect evidence about the association of C-reactive protein with Peripheral Arterial Disease, using keywords like C-reactive protein, hs-C-reactive protein, inflammation, atherogenesis, peripheral arterial disease and their combinations. Out of 240 articles shown during online search on PubMed, only 17 articles related to the role of CRP and High sensitivity CRP (hs-CRP) as a marker in PAD. Results: 17 articles based on the role of CRP and High sensitivity CRP (hs-CRP) as a marker in PAD were studied and evaluated thoroughly working on their study design and outcomes. Almost all the 17 studies showed strong association hs-CRP with PAD. The results are described in the form of a table. Conclusion: CRP seems to be a marker of severity of PAD and it may serve as a strong prognostic indicator.